Structurization of educational expedition studies in the form of taxonomies (Educational Dimension, 2022)
High volume and low level of data structuring cause problems with data processing nowadays. The scope of perspective to provide such structuring is scientific studies because, in most cases, they provide predicted measurement parameters, and it’s easy to structure. As a result, the parameters that will be measured can be defined and forms prepared for completion during studies. As a result, the parameters that will be measured can be defined and forms prepared for completion during shipping. This study corroborates how to handle this data in ontologies, providing structuring and interoperability of data. The case of the use of such an approach based on the expedition of real-life environmental study during Junior Academy of Sciences of Ukraine expedition is described. The approach uses Excel-based templates to be filled during the measurement of parameters. Each line in such an array represents the location or name of the search subject. An extra column is dedicated to geolocation insertion. After providing the research, such files are uploaded into the Polyhedron system, and ontology is generated. These ontologies are stored and integrated into ArcGis and can be used to present their own findings and provide basic searches by other researchers. The process of integrating a few ontologies that used a proposed template from different expeditions is described. Additional, as such studies are also used IMRAD, it is possible to use the approach of using IMRAD as the core of the expedition result’s graph and use the expedition studies in the same structure as other.
Keywords: ontology; ontological journal; scientific method; science; geoinformation systems; GIS; student; cognitive IT Polyhedron